Asthma Exacerbations and Symptom Variability in Children Due to Short-term Ambient Air Pollution Changes in Ostrava, Czech Republic - Velická, Helena; Puklová, Vladimíra; Keder, Josef; Brabec, Marek; Malý, Marek; Bobák, Martin; Kotlík, Bohumil; Jiřík, Vítězslav; Janout, Vladimír; Kazmarová, Helena (Central European journal of public health, 2015)
AIM: The Ostrava region suffers from high levels of air pollution during winter inversions. We investigated the association between short-term elevations of air pollutant concentrations and worsening of respiratory problems, use of asthma medication and restriction of daily activities in asthmatic patients in Ostrava. METHODS: One-hundred and forty-seven child and adolescent patients (aged 6-18 years) with a confirmed diagnosis of mild to moderate persistent asthma were included in the study. Participants' parents completed diaries covering the period of November 2013 to February 2014; this analysis included 18,228 person-days. Daily smoothed maps of outdoor concentrations of particulate matter (PM10), nitrogen dioxide (NO2) and sulphur dioxide (SO2) were constructed from routine monitoring data, and participants' daily exposures were estimated on the basis of time spent at home and at school. The associations between health outcomes and exposure to air pollutants were estimated using the multiple logistic regression method. RESULTS: The odds ratios (OR) of the combined outcome for wheezing and/or difficulty in breathing, per 10 µg/m³ increase in the mean 24-h exposure were 1.07 (95% confidence interval 1.04-1.11) for PM10, 1.30 (1.18-1.44) for NO2, and 1.37 (1.18-1.59) for SO2. Additional inhaler use (in addition to usual medication) was also more frequent at higher air pollutant concentrations; the odds ratios per 10 µg/m³ increase in the mean 24-h exposure were 1.05 (1.02-1.07) for PM10, 1.19 (1.10-1.30) for NO2, and 1.26 (1.11-1.43) for SO2. Associations were less consistent for other health outcomes. CONCLUSIONS: These results suggest moderately strong associations between air pollutant concentrations and respiratory difficulties among asthmatic children and adolescents. More detailed analyses are required to confirm these preliminary findings.
Keywords: Asthma; bronchiální astma; Humans; dítě; Child; Female; rizikové faktory; vystavení vlivu životního prostředí; children; short-term exposure; lidé; Air Pollution; Air Pollutants; asthma; látky znečišťující vzduch; respiratory symptoms; ženské pohlaví; stupeň závažnosti nemoci; Male; Adolescent; air pollution; Czech Republic; Severity of Illness Index; Environmental Exposure; znečištění ovzduší; Česká republika; mužské pohlaví; mladiství; Risk Factors